2021
DOI: 10.3390/ijms22063124
|View full text |Cite
|
Sign up to set email alerts
|

Beta-1,3 Oligoglucans Specifically Bind to Immune Receptor CD28 and May Enhance T Cell Activation

Abstract: Beta glucans are known to have immunomodulatory effects that mediated by a variety of mechanisms. In this article, we describe experiments and simulations suggesting that beta-1,3 glucans may promote activation of T cells by a previously unknown mechanism. First, we find that treatment of a T lymphoblast cell line with beta-1,3 oligoglucan significantly increases mRNA levels of T cell activation-associated cytokines, especially in the presence of the agonistic anti-CD3 antibody. This immunostimulatory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Interestingly, recent research has shown that β-glucans may stimulate an immune response by binding to CD28 on the surface of T cells and that this stimulation is potentiated by CD3 activation. Cormer and colleagues explored interactions of β-1,3 glucans with the CD28 receptor and found that glucan molecules insert themselves into a channel on the surface of CD28 and moreover diffuse around the receptor, coming into contact with different regions of the protein [ 62 ]. This is another potential mechanism underlying the observed immunomodulatory effects of Se-Le-30.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent research has shown that β-glucans may stimulate an immune response by binding to CD28 on the surface of T cells and that this stimulation is potentiated by CD3 activation. Cormer and colleagues explored interactions of β-1,3 glucans with the CD28 receptor and found that glucan molecules insert themselves into a channel on the surface of CD28 and moreover diffuse around the receptor, coming into contact with different regions of the protein [ 62 ]. This is another potential mechanism underlying the observed immunomodulatory effects of Se-Le-30.…”
Section: Discussionmentioning
confidence: 99%
“…The properties and benefits of algal compounds with nutraceutical, pharmacological, and biomedical interest [ 2 , 3 ] are the main topics of this Special Issue in International Journal of Molecular Sciences , with major emphasis on polysaccharides, of which are the most exploited compounds worldwide. This main topic is expanded to include polysaccharides of other origins, such as fungi [ 4 , 5 ], which also possess biological activity, and review the defense mechanisms triggered by the interaction of these compounds with organisms, which are at the base of immunity [ 6 ].…”
mentioning
confidence: 99%
“…Comer et al [ 3 ] tested two 5-mer oligoglucans (β-1,3 laminaripentaose, and α-1,4 maltopentaose) for their capacity to induce cytokine expression. They verified an immune-stimulant effect of β-1,3 oligoglucans on T lymphocytes, with a significant increase in the mRNA levels of T-cell-activation-associated cytokines, especially in the presence of the agonistic anti-CD3 antibody and the absence of dectin-1.…”
mentioning
confidence: 99%